The Sacha Inchi (Plukenetia volubilis) Research Trends for Health - Jaja Jamaludin (Sean Institute, 2025)
This article aims to analyze the health benefits of Sacha Inchi (Plukenetia volubilis) based on Scopus indexed scientific literature with a systematic literature review (SLR) approach. The research was conducted using VOSviewer software to map the relationship between the main topics in the literature studied. Of the 20 selected articles, the analysis showed that the most frequently discussed topics were nutritional content (omega-3, omega-6, and protein), benefits for heart health, skin, and brain function, and potential weight management. This study provides insight into Sacha Inchi's research trends and identifies research gaps for future studies.